2011
DOI: 10.1007/s10530-011-0010-2
|View full text |Cite
|
Sign up to set email alerts
|

Invasiveness of an introduced species: the role of hybridization and ecological constraints

Abstract: Introduced species are confronted with new environments to which they need to adapt. However, the ecological success of an introduced species is generally difficult to predict, especially when hybridizations may be involved in the invasion success. In western Europe, the lake frog Pelophylax ridibundus appears to be particularly successful. A reason for this species' success might be the presence of the invader's genetic material prior to the introduction in the form of a hybrid between P. ridibundus and a sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…To our knowledge, our study is the first to assess the potential impact of colonization by alien PR on native amphibians in western Europe that are not phylogenetically closely related ranids of PR (Luquet et al 2011). The results indicate that native BV and invasive PR rarely cohabit on the riverbanks of the mountain rivers in the study area.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…To our knowledge, our study is the first to assess the potential impact of colonization by alien PR on native amphibians in western Europe that are not phylogenetically closely related ranids of PR (Luquet et al 2011). The results indicate that native BV and invasive PR rarely cohabit on the riverbanks of the mountain rivers in the study area.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, previous studies have shown that PR occupies larger habitats, such as dead arms, gravel pits and lakes (Pagano et al 2001;Van Buskirk 2003), as well as small water bodies such as ponds in gravel beds (Joly and Morand 1994;Morand and Joly 1995). PR tadpoles require high dissolved oxygen rates, which are provided by strong river influence (Luquet et al 2011). In addition, PR often occurs in permanent water bodies with a high density of predator fishes (Van Buskirk 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inbreeding (Vander Wal et al ), outbreeding (Frankham et al ), hybridization (Luquet et al ), selection, and adaptation (Hohenlohe et al ) are central influences on evolutionary processes affecting population persistence (Table ). Early researchers used effective population size ( N e ) to assess genetic population viability and evolutionary potential (Frankel & Soulé ; Reed et al ; Nunney & Elam ).…”
Section: Incorporating Eco‐evolutionary Processes In Pvasmentioning
confidence: 99%
“…To this aim, we adapted and implemented a model of interspecific hybridization without genetic introgression that we have recently developed (Quilodr an et al 2014). The case study of biological invasion reinforced by nonintrogressive hybridization that we investigated here is the colonization of Western Europe by the waterfrog Pelophylax ridibundus coming either from Central or Southern Europe (Holsbeek and Jooris 2010), apparently mediated by human activities (Luquet et al 2011). In France and Switzerland, this waterfrog was introduced during the 20th century for frog legs consumption and for scientific purposes.…”
Section: Introductionmentioning
confidence: 99%